Utilization of organic phosphorus sources by oilseed rape, sunflower, and soybean. Issue 2 (2nd February 2015) - Belinque, Hernan; Pucheu, Norma; Kerber, Norma; Rubio, Gerardo
Abstract: We evaluated the ability of Brassica napus L. (oilseed rape), Helianthus annus L. (sunflower), and Glycine max L. (soybean) plants grown inoculated with or without bacteria to utilize organic P sources. Plants were supplied with inorganic (dibasic sodium phosphate) and organic P sources (phytate and glucose phosphate) at three concentrations and grown for 40 d under sterile conditions. Three inoculation treatments were compared: control (non‐inoculated plants), inoculation with Bacillus amyloliquefaciens BNM340, and inoculation with Pseudomonas fluorescens BNM296 (two bacteria with proven phytase activity). Oilseed rape, sunflower and soybean could utilize organic P sources. For example, when phytate (0.5 mM) P was used as the external P source, the increase factors over the no‐P treatments were 4.5, 1.4, and 1.4 for oilseed rape, sunflower, and soybean P uptake, respectively. When glucose 1‐phosphate disodium salt (G1P, 0.5 mM) was the P source, the increase factors were 8.8, 1.7, and 1.9 respectively. Positive responses to the organic P sources were found for the biomass accumulation of oilseed rape and soybean but not for sunflower. The inoculation with bacteria did not exert a promoting effect on P uptake. We demonstrate that the three species can effectively use organic P sources. The existence of crop plants that are more efficient in the utilization of different soil P sources would be particularly beneficial to improve P recycling and use of P fertilizers in agriculture.